The Role of Banjar Ethnic Community Leaders in the Cultural Development of Rawak Hilir Village, Sekadau Hulu District, Sekadau Regency - Sofian, Ilham Nur; Zakso, Amrazi; Firmansyah, Andang (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to examine the role of Banjar ethnic community leaders in the cultural development of Rawak Hilir Village, Sekadau Hulu District, Sekadau Regency. This research uses historical research methods consisting of topic selection, heuristics, verification, interpretation, and historiography. The results of the study indicate that Banjar ethnic community leaders in Rawak Hilir Village have a significant role in the development of local culture, such as in the preservation of traditions, the development of arts, religious growth, and the maintenance of cultural values. This study also found that the role of Banjar ethnic community leaders in cultural development in Rawak Hilir Village is influenced by factors such as education and interaction with other communities. This research is expected to contribute to the cultural heritage, as well as the understanding of the role of Banjar ethnic community figures in the development of local culture, and can be used as a reference for further research and for the development of culture in Sekadau Regency.